Transformasi Digital Lintas Sektor untuk Daya Saing Ekonomi Pesisir Kabupaten Banyuwangi - Lintang Rahmayana; Khoirina Fajriani (Jurnal Riset Perencanaan Wilayah dan Kota, 2026)
Abstract. Digitalization is increasingly viewed as an important strategy for strengthening the economic competitiveness of coastal regions, although its implementation remains uneven and highly contextual. This study aims to analyze the digitalization process across economic sectors and its implications for local competitiveness in Banyuwangi Regency. The research employed a qualitative approach through in-depth interviews with actors in the fisheries, agriculture, trade, tourism, MSME sectors, and local government. Data were analyzed using thematic coding to identify the driving factors, implementation patterns, benefits, challenges, and impacts of digitalization. The findings show that digitalization has developed across multiple sectors and has contributed to broader market access, increased productivity, improved governance, and stronger regional reputation. However, digitalization still faces challenges related to infrastructure limitations, digital literacy gaps, and resistance to change. The success of digitalization is supported by the synergy between government initiatives and community-based innovations implemented in an inclusive and adaptive manner. Abstrak. Digitalisasi semakin dipandang sebagai strategi penting dalam memperkuat daya saing ekonomi wilayah pesisir, namun implementasinya bersifat tidak merata dan kontekstual. Penelitian ini bertujuan menganalisis proses digitalisasi sektor ekonomi dan implikasinya terhadap daya saing lokal di Kabupaten Banyuwangi. Penelitian menggunakan pendekatan kualitatif melalui wawancara mendalam dengan pelaku perikanan, pertanian, perdagangan, pariwisata, UMKM, dan pemerintah daerah. Analisis dilakukan dengan pengkodingan tematik untuk mengidentifikasi faktor pendorong, pola implementasi, manfaat, tantangan, dan dampak digitalisasi. Hasil penelitian menunjukkan bahwa digitalisasi berkembang secara multisektoral dan memberikan manfaat berupa perluasan akses pasar, peningkatan produktivitas, perbaikan tata kelola, serta penguatan reputasi wilayah. Namun, digitalisasi masih menghadapi hambatan infrastruktur, kesenjangan literasi digital, dan resistensi perubahan. Keberhasilan digitalisasi ditopang oleh sinergi inisiatif pemerintah dan inovasi komunitas secara inklusif dan adaptif.